Stress Measurement of Steel Strands Based on System Identification Method - Ji Qian; Jianbin Li; Changchun Li; Jianting Zhou; Guowen Yao (Shock and Vibration)
Steel strands are crucial components of a prestressed structure, but their performance degrades inevitably with time. Among the existing nondestructive testing methods for measuring the stress state of steel strands, ultrasonic guided wave methods have received the most research attention and are most likely to be applied to actual engineering. This work views the propagation of ultrasonic guided wave as an individual system, and the variations in the stress state in steel strands can be related to the parameters gained by the system identification model. The finite element simulation and experimental results show the propagation characteristics of the guided wave are influenced distinctly by the stress state. The index constructed by the system parameters exhibits good monotonic linear with stress level variation, and the slope of the fitted line from experimental data is similar to the simulation result. The sensor placement and loading path have a limited effect on the stress state and the proposed index.